Learning Cities Multimodal Explorations and Placed Pedagogies (Cultural Studies and Transdisciplinarity in Education,, 2018)
This book is an interdisciplinary text exploring the learning and educative potentials of cities and their spaces, including urban and suburban contexts, at all stages of life. Drawing on the insights of researchers from diverse fields, such as education, architecture, history, visual sociology, applied linguistics and sensory studies, this collection of papers develops and demonstrates the connection between experience, in all its dimensions, and informal learning in the city. The chapters discuss various sensory domains of experience, considering visual, embodied, and even sexual dimensions in relation to what and how learning operates, and the contributors reflect on their learning and inquiring experiences in the city, with special reference to topics such as narrativity, 'race' and ethnicity, equity, urban literacy, re-generation, participation, representation and oral histories.